Moderate to severe gambling problems and traumatic brain injury: A population-based study. (February 2019) - Turner, Nigel E.; McDonald, André J.; Ialomiteanu, Anca R.; Mann, Robert E.; McCready, John; Millstone, Dov; Hamilton, Hayley; Elton-Marshall, Tara; Rehm, Jurgen; Kurdyak, Paul; Ilie, Gabriela; Wickens, Christine M.; et al.
Highlights: Traumatic brain injury (TBI) is a common injury. Study based on a general population survey of adults ages 18+ from Ontario, Canada ( N  = 3809). Adjusted odds ratio (AOR) indicates that people with TBI are 2.8 more likely to have a gambling problem (controlling for all other variables in the model). People who report psychological distress are 2.7 times more likely to also report a gambling problem. People who engage in hazardous drinking 2.7 times more likely to also report a gambling problem. Abstract: Traumatic brain injury (TBI) is a common injury characterized by a change in brain function after an external blow to the head and is associated with substance abuse, psychological distress, risk-taking, and impulsivity. Convenience and clinical samples have also linked TBI to problem gambling, but have not ruled out confounding variables such as hazardous drinking and psychological distress. This study examines the relationship between TBI and moderate to severe problem gambling in a general population probability sample controlling for hazardous drinking and psychological distress. The data were obtained from a 2015–2016 cross-sectional general population telephone survey of adults ages 18+from Ontario, Canada ( N  = 3809). Logistic regression was used to estimate the association as adjusted odds ratios (AOR). Moderate to severe problem gambling was independently associated with a history of TBI after adjusting for potential confounders (AOR: 2.80), and had a statistically significant relationship with psychological distress (AOR = 2.74), hazardous drinking (AOR = 2.69), and lower educational levels (AOR = 0.37). This study provides further data to suggest a link between TBI and moderate to severe problem gambling; however, more research is needed to determine if there is a causal relationship or the potential implications for prevention and treatment.